Contemporary Legal Issues Affecting Professional in Human Service Fields. - Killion, Susan (1992)
Keywords: dept.nur; faculty_collection

Dual assignment: An alternative clinical teaching strategy - Fugate, T.; Rebeschi, L.M. (Nurse Educator, 1992)
Meeting students’ learning needs in acute care settings is challenging. The authors discuss dual assignment in the pediatric setting with beginning nursing students. © 1992 Lippincott-Raven Publishers.
Keywords: Clinical Competence; Education, Nursing, Baccalaureate; Human; Pediatric Nursing; article; competence; dept.nur; education; human; methodology; nursing; nursing education; standard

AIDS education on the college campus: Roy's adaptation model directs inquiry - Vicenzi, Angela E; Thiel, Robert (Public Health Nursing, 1992)
We assessed the beliefs of 49 college students regarding the acquired immunodeficiency syndrome (AIDS), condom use, and sexual behaviors related to AIDS prevention. Roy's modes of self-concept, interdependence, and role function were used as a framework to find psychosocial determinants that influence safer sex practices. Interdependence was measured by a sexual regard scale. Beliefs regarding both AIDS beliefs and condom were very positive. Students were selectively using safer sex practices; most reported avoiding high-risk partners, but only 39% were using condoms. No significant associations were found among the four independent measures of AIDS beliefs, condom beliefs, self-esteem, and sexual regard or with the dependent measure, AIDS safer sex practices. A two-hour safer sex educational module did change several beliefs but did not increase safer sex practices. Most participating students stated they had a good understanding of how AIDS was spread, they knew how to use condoms correctly, and they discussed AIDS with friends and parents.
Keywords: dept.nur

Collaborative project to examine social support in elder homebound diabetics - Zink, Margo R; Gadomski, Mary; Oconnell, Patricia Buckley; Nizziherzog, Marie (Home Health Care Management & Practice, 1992)
Social support has a significant effect on the response to illness and treatment. The au thors present some of the findings and practical applications originating from a collaborative study, including a clinical indicator tool for the diabetic patient. This information gives the home health care professional an expanded knowledgebase to use in developing individualized care plans for the elder home care diabetic. © 1992, Sage Publications. All rights reserved.
Keywords: dept.nur